Electrospun one-dimensional nanostructures: a new horizon for gas sensing materials - Imran, Muhammad; Motta, Nunzio; Shafiei, Mahnaz (Beilstein Journal of Nanotechnology, 2018)
Electrospun one-dimensional (1D) nanostructures are rapidly emerging as key enabling components in gas sensing due to their unique electrical, optical, magnetic, thermal, mechanical and chemical properties. 1D nanostructures have found applications in numerous areas, including healthcare, energy storage, biotechnology, environmental monitoring, and defence/security. Their enhanced specific surface area, superior mechanical properties, nanoporosity and improved surface characteristics (in particular, uniformity and stability) have made them important active materials for gas sensing applications. Such highly sensitive and selective elements can be embedded in sensor nodes for internet-of-things applications or in mobile systems for continuous monitoring of air pollutants and greenhouse gases as well as for monitoring the well-being and health in everyday life. Herein, we review recent developments of gas sensors based on electrospun 1D nanostructures in different sensing platforms, including optical, conductometric and acoustic resonators. After explaining the principle of electrospinning, we classify sensors based on the type of materials used as an active sensing layer, including polymers, metal oxide semiconductors, graphene, and their composites or their functionalized forms. The material properties of these electrospun fibers and their sensing performance toward different analytes are explained in detail and correlated to the benefits and limitations for every approach.
Keywords: 1D nanostructures; conductometric devices; electrospinning; gas sensors; optical sensors; resonators

(untitled) - Koo, W.-T.; Choi, S.-J.; Kim, S.-J.; Jang, J.-S.; Tuller, H. L.; Kim, I.-D. (J. Am. Chem. Soc., 2016)

(untitled) - Long, Y.; Chen, H.; Wang, H.; Peng, Z.; Yang, Y.; Zhang, G.; Li, N.; Liu, F.; Pei, J. (Anal. Chim. Acta, 2012)

(untitled) - Long, Y.; Chen, H.; Yang, Y.; Wang, H.; Yang, Y.; Li, N.; Li, K.; Pei, J.; Liu, F. (Macromolecules, 2009)

(untitled) - Wang, T.; Ma, S.; Cheng, L.; Luo, J.; Jiang, X.; Jin, W. (Sens. Actuators, B, 2015)

(untitled) - Cheng, L.; Ma, S.; Li, X.; Luo, J.; Li, W.; Li, F.; Mao, Y.; Wang, T.; Li, Y. (Sens. Actuators, B, 2014)

(untitled) - Wang, C.; Ma, S.; Sun, A.; Qin, R.; Yang, F.; Li, X.; Li, F.; Yang, X. (Sens. Actuators, B, 2014)

(untitled) - Li, W.; Ma, S.; Li, Y.; Li, X.; Wang, C.; Yang, X.; Cheng, L.; Mao, Y.; Luo, J.; Gengzang, D.; Wan, G.; Xu, X. (J. Alloys Compd., 2014)

(untitled) - Mohanapriya, P.; Segawa, H.; Watanabe, K.; Watanabe, K.; Samitsu, S.; Natarajan, T.; Jaya, N. V.; Ohashi, N. (Sens. Actuators, B, 2013)

(untitled) - Liu, D.; Liu, T.; Zhang, H.; Lv, C.; Zeng, W.; Zhang, J. (Mater. Sci. Semicond. Process., 2012)

(untitled) - Liu, C.; Shan, H.; Liu, L.; Li, S.; Li, H. (Ceram. Int., 2014)

(untitled) - Wan, G.; Ma, S.; Li, X.; Li, F.; Bian, H.; Zhang, L.; Li, W. (Mater. Lett., 2014)

Nanotechnology-Enabled Sensors - Kalantar-zadeh, K.; Fry, B. (Springer US, 2008)

Solid state gas sensing - Comini, E.; Faglia, G.; Sberveglieri, G. (Springer, 2009)

Chemical sensors: an introduction for scientists and engineers - Gründler, P. (Springer, 2007)

(untitled) - Bahreyni, B.; Shafai, C. (Sens. Actuators, A, 2007)

(untitled) - Khoshaman, A. H.; Bahreyni, B. (Sens. Actuators, B, 2012)

(untitled) - Zheng, J.; Li, G.; Ma, X.; Wang, Y.; Wu, G.; Cheng, Y. (Sens. Actuators, B, 2008)

(untitled) - Xie, J.; Wang, H.; Duan, M. (Sens. Actuators, B, 2014)

(untitled) - Minh, V. A.; Tuan, L. A.; Huy, T. Q.; Hung, V. N.; Quy, N. V. (Appl. Surf. Sci., 2013)

(untitled) - Khoshaman, A. H.; Li, P. C.; Merbouh, N.; Bahreyni, B. (Sens. Actuators, B, 2012)

(untitled) - Wang, X.; Cui, F.; Lin, J.; Ding, B.; Yu, J.; Al-Deyab, S. S. (Sens. Actuators, B, 2012)

(untitled) - Shafiei, M.; Hoshyargar, F.; Lipton-Duffin, J.; Piloto, C.; Motta, N.; O’Mullane, A. P. (J. Phys. Chem. C, 2015)

(untitled) - Shafiei, M.; Sadek, A.; Yu, J.; Latham, K.; Breedon, M.; McCulloch, D.; Kalantar-zadeh, K.; Wlodarski, W. (Sens. Lett., 2011)

(untitled) - Shafiei, M.; Spizzirri, P. G.; Arsat, R.; Yu, J.; du Plessis, J.; Dubin, S.; Kaner, R. B.; Kalantar-zadeh, K.; Wlodarski, W. (J. Phys. Chem. C, 2010)

(untitled) - Yu, J.; Chen, G.; Li, C. X.; Shafiei, M.; Ou, J. Z.; Plessis, J. d.; Kalantar-zadeh, K.; Lai, P. T.; Wlodarski, W. (Sens. Actuators, A, 2011)

(untitled) - Yaacob, M. H.; Ahmad, M. Z.; Sadek, A. Z.; Ou, J. Z.; Campbell, J.; Kalantar-zadeh, K.; Wlodarski, W. (Sens. Actuators, B, 2013)

(untitled) - Jane, H.; Ralph, P. T. (Meas. Sci. Technol., 2013)

(untitled) - Arsat, R.; Breedon, M.; Shafiei, M.; Spizziri, P. G.; Gilje, S.; Kaner, R. B.; Kalantar-zadeh, K.; Wlodarski, W. (Chem. Phys. Lett., 2009)

(untitled) - Shafiei, M.; Yu, J.; Chen, G.; Lai, P. T.; Motta, N.; Wlodarski, W.; Kalantar-zadeh, K. (Sens. Actuators, B, 2013)

(untitled) - Shafiei, M.; Hoshyargar, F.; Motta, N.; O'Mullane, A. P. (Mater. Des., 2017)

(untitled) - Hoshyargar, F.; Shafiei, M.; Piloto, C.; Motta, N.; O'Mullane, A. P. (J. Mater. Chem. C, 2016)

(untitled) - Ding, B.; Wang, M.; Yu, J.; Sun, G. (Sensors, 2009)

(untitled) - Shafiei, M.; Yu, J.; Arsat, R.; Kalantar-zadeh, K.; Comini, E.; Ferroni, M.; Sberveglieri, G.; Wlodarski, W. (Sens. Actuators, B, 2010)

(untitled) - Comini, E. (Mater. Today, 2016)

(untitled) - Liang, H.-W.; Liu, S.; Yu, S.-H. (Adv. Mater., 2010)

(untitled) - Liu, J.-W.; Liang, H.-W.; Yu, S.-H. (Chem. Rev., 2012)

(untitled) - Teo, W. E.; Ramakrishna, S. (Nanotechnology, 2006)

(untitled) - Ramakrishna, S.; Fujihara, K.; Teo, W.-E.; Yong, T.; Ma, Z.; Ramaseshan, R. (Mater. Today, 2006)

(untitled) - Crespy, D.; Friedemann, K.; Popa, A.-M. (Macromol. Rapid Commun., 2012)

(untitled) - Zhang, C.-L.; Yu, S.-H. (Chem. Soc. Rev., 2014)

Electrospinning process and nanofiber research - Haghi, A.; Zaikov, G. E. (Nova Science Publishing, 2011)

(untitled) - Ding, B.; Wang, M.; Wang, X.; Yu, J.; Sun, G. (Mater. Today, 2010)

(untitled) - Choi, S.-J.; Persano, L.; Camposeo, A.; Jang, J.-S.; Koo, W.-T.; Kim, S.-J.; Cho, H.-J.; Kim, I.-D.; Pisignano, D. (Macromol. Mater. Eng., 2017)

On the Magnet, Magnetick Bodies Also, and on the Great Magnet the Earth: A New Physiology, Demonstrated by Many Arguments & Experiments - Gilbert, W.; Thompson, S. P. (Chiswick Press, 1900)

(untitled) - Tucker, N.; Stanger, J. J.; Staiger, M. P.; Razzaq, H.; Hofman, K. J. (Eng. fibres Fabr., 2012)

(untitled) - Chronakis, I. S. (J. Mater. Process. Technol., 2005)

(untitled) - Li, D.; Xia, Y. (Adv. Mater., 2004)

(untitled) - Taylor, G. (Proc. R. Soc. London, Ser. A, 1964)

(untitled) - Reneker, D. H.; Yarin, A. L.; Fong, H.; Koombhongse, S. (J. Appl. Phys., 2000)

(untitled) - Doshi, J.; Reneker, D. H. (J. Electrost., 1995)

(untitled) - Tomer, V.; Teye-Mensah, R.; Tokash, J. C.; Stojilovic, N.; Kataphinan, W.; Evans, E. A.; Chase, G. G.; Ramsier, R. D.; Smith, D. J.; Reneker, D. H. (Sol. Energy Mater. Sol. Cells, 2005)

(untitled) - Zhang, G.; Kataphinan, W.; Teye-Mensah, R.; Katta, P.; Khatri, L.; Evans, E.; Chase, G. G.; Ramsier, R.; Reneker, D. (Mater. Sci. Eng., B, 2005)

(untitled) - Shin, C.; Chase, G. G.; Reneker, D. H. (Colloids Surf., A, 2005)

(untitled) - Putthanarat, S.; Eby, R.; Kataphinan, W.; Jones, S.; Naik, R.; Reneker, D.; Farmer, B. (Polymer, 2006)

(untitled) - Lannutti, J.; Reneker, D.; Ma, T.; Tomasko, D.; Farson, D. (Mater. Sci. Eng., C, 2007)

(untitled) - Deitzel, J.; Kleinmeyer, J.; Hirvonen, J.; Tan, N. B. (Polymer, 2001)

(untitled) - Shafiei, M.; El-chami, I.; Rintoul, L.; Bahreyni, B. (Mater. Des., 2017)

(untitled) - Bhardwaj, N.; Kundu, S. C. (Biotechnol. Adv., 2010)

(untitled) - Jacobs, V.; Anandjiwala, R. D.; Maaza, M. (J. Appl. Polym. Sci., 2010)

(untitled) - Deitzel, J.; Kleinmeyer, J.; Harris, D.; Beck Tan, N. (Polymer, 2001)

(untitled) - Son, W. K.; Youk, J. H.; Lee, T. S.; Park, W. H. (Polymer, 2004)

Proceedings of Macromolecular Symposia - Righi, T. M.; Almeida, R. S.; d'Ávila, M. A. (Electrospinning of gelatin/PEO blends: Influence of process parameters in the nanofiber properties, 2012)

(untitled) - Chen, H.; Di, J.; Wang, N.; Dong, H.; Wu, J.; Zhao, Y.; Yu, J.; Jiang, L. (Small, 2011)

(untitled) - Nirmala, R.; Jeon, K. S.; Lim, B. H.; Navamathavan, R.; Kim, H. Y. (Ceram. Int., 2013)

(untitled) - Verdejo, R.; Bernal, M. M.; Romasanta, L. J.; Lopez-Manchado, M. A. (J. Mater. Chem., 2011)

(untitled) - Wang, Q.; Du, Y.; Feng, Q.; Huang, F.; Lu, K.; Liu, J.; Wei, Q. (J. Appl. Polym. Sci., 2013)

(untitled) - Das, S.; Wajid, A. S.; Bhattacharia, S. K.; Wilting, M. D.; Rivero, I. V.; Green, M. J. (J. Appl. Polym. Sci., 2013)

(untitled) - Bao, Q.; Zhang, H.; Yang, J.-x.; Wang, S.; Tang, D. Y.; Jose, R.; Ramakrishna, S.; Lim, C. T.; Loh, K. P. (Adv. Funct. Mater., 2010)

(untitled) - Lin, T.; Wang, H.; Wang, X. (Adv. Mater., 2005)

(untitled) - Viswanathamurthi, P.; Bhattarai, N.; Kim, H.; Lee, D.; Kim, S.; Morris, M. (Chem. Phys. Lett., 2003)

(untitled) - Shao, C.; Yang, X.; Guan, H.; Liu, Y.; Gong, J. (Inorg. Chem. Commun., 2004)

(untitled) - Liu, Z.; Sun, D. D.; Guo, P.; Leckie, J. O. (Nano Lett., 2007)

(untitled) - Li, D.; McCann, J. T.; Xia, Y. (Small, 2005)

(untitled) - Li, D.; Xia, Y. (Nano Lett., 2004)

(untitled) - Choi, S.-J.; Chattopadhyay, S.; Kim, J. J.; Kim, S.-J.; Tuller, H. L.; Rutledge, G. C.; Kim, I.-D. (Nanoscale, 2016)

(untitled) - Fan, X.-X.; He, X.-L.; Li, J.-P.; Gao, X.-G.; Jia, J. (Vacuum, 2016)

(untitled) - Jun, J.; Lee, J. S.; Shin, D. H.; Oh, J.; Kim, W.; Na, W.; Jang, J. (J. Mater. Chem. A, 2017)

(untitled) - Liang, X.; Jin, G.; Liu, F.; Zhang, X.; An, S.; Ma, J.; Lu, G. (Ceram. Int., 2015)

(untitled) - Liu, L.; Li, S.; Guo, X.; Wang, L.; Liu, L.; Wang, X. (J. Mater. Sci.: Mater. Electron., 2016)

(untitled) - Li, Z.; Fan, Y.; Zhan, J. (Eur. J. Inorg. Chem., 2010)

(untitled) - Luzio, A.; Canesi, E.; Bertarelli, C.; Caironi, M. (Materials, 2014)

2015 International Conference on Proceedings of Industrial Engineering and Operations Management (IEOM) - Nair, V.; Regius, F.; Ragavendar, A.; Suman, S. (Role of electrospun ZnO-NiO metaloxide nanocomposite fibres for sensor applications, 2015)

(untitled) - Khalil, A.; Kim, J. J.; Tuller, H. L.; Rutledge, G. C.; Hashaikeh, R. (Sens. Actuators, B, 2016)

(untitled) - Macías, M.; Chacko, A.; Ferraris, J. P.; Balkus, K. J., Jr (Microporous Mesoporous Mater., 2005)

(untitled) - Tian, W.; Zhai, T.; Zhang, C.; Li, S.-L.; Wang, X.; Liu, F.; Liu, D.; Cai, X.; Tsukagoshi, K.; Golberg, D.; Bando, Y. (Adv. Mater., 2013)

(untitled) - Xu, S.; Kan, K.; Yang, Y.; Jiang, C.; Gao, J.; Jing, L.; Shen, P.; Li, L.; Shi, K. (J. Alloys Compd., 2015)

(untitled) - Ji, S.; Li, Y.; Yang, M. (Sens. Actuators, B, 2008)

Proceedings of 2006 Sixth IEEE Conference on Nanotechnology - Gopalan, A.; Lee, K.-P.; Manian, K.; Santhosh, P.; Song, K.-D.; Lee, D.-D. (Fabrication of functional nanofibrous ammonia sensor, 2006)

(untitled) - Abideen, Z. U.; Katoch, A.; Kim, J.-H.; Kwon, Y. J.; Kim, H. W.; Kim, S. S. (Sens. Actuators, B, 2015)

(untitled) - Fratoddi, I.; Venditti, I.; Cametti, C.; Russo, M. V. (Sens. Actuators, B, 2015)

Solid State Gas Sensing - Comini, E.; Faglia, G.; Sberveglieri, G. (Electrical-Based Gas Sensing, 2009)

(untitled) - Zhang, J.; Liu, X.; Neri, G.; Pinna, N. (Adv. Mater., 2016)

(untitled) - Bian, H.; Ma, S.; Sun, A.; Xu, X.; Yang, G.; Gao, J.; Zhang, Z.; Zhu, H. (Superlattices Microstruct., 2015)

(untitled) - Park, J.-A.; Moon, J.; Lee, S.-J.; Kim, S. H.; Zyung, T.; Chu, H. Y. (Mater. Lett., 2010)

(untitled) - Park, J.-A.; Moon, J.; Lee, S.-J.; Kim, S. H.; Zyung, T.; Chu, H. Y. (Thin Solid Films, 2010)

(untitled) - Leng, J.-y.; Xu, X.-j.; Lv, N.; Fan, H.-t.; Zhang, T. (J. Colloid Interface Sci., 2011)

(untitled) - Lu, X.; Liu, X.; Zhang, W.; Wang, C.; Wei, Y. (J. Colloid Interface Sci., 2006)

(untitled) - Nguyen, T.-A.; Jun, T.-S.; Rashid, M.; Kim, Y. S. (Mater. Lett., 2011)

(untitled) - Sungpanich, J.; Thongtem, T.; Thongtem, S. (Mater. Lett., 2011)

(untitled) - Giancaterini, L.; Emamjomeh, S. M.; De Marcellis, A.; Palange, E.; Cantalini, C. (Procedia Eng., 2015)

(untitled) - Bai, X.; Ji, H.; Gao, P.; Zhang, Y.; Sun, X. (Sens. Actuators, B, 2014)

(untitled) - Chi, X.; Liu, C.; Liu, L.; Li, Y.; Wang, Z.; Bo, X.; Liu, L.; Su, C. (Sens. Actuators, B, 2014)

(untitled) - Feng, C.; Li, X.; Ma, J.; Sun, Y.; Wang, C.; Sun, P.; Zheng, J.; Lu, G. (Sens. Actuators, B, 2015)

(untitled) - Feng, C.; Wang, C.; Cheng, P.; Li, X.; Wang, B.; Guan, Y.; Ma, J.; Zhang, H.; Sun, Y.; Sun, P.; Zheng, J.; Lu, G. (Sens. Actuators, B, 2015)

(untitled) - Giancaterini, L.; Emamjomeh, S. M.; De Marcellis, A.; Palange, E.; Resmini, A.; Anselmi-Tamburini, U.; Cantalini, C. (Sens. Actuators, B, 2016)

(untitled) - Kim, N.-H.; Choi, S.-J.; Kim, S.-J.; Cho, H.-J.; Jang, J.-S.; Koo, W.-T.; Kim, M.; Kim, I.-D. (Sens. Actuators, B, 2016)

(untitled) - Kim, N.-H.; Choi, S.-J.; Yang, D.-J.; Bae, J.; Park, J.; Kim, I.-D. (Sens. Actuators, B, 2014)

(untitled) - Nguyen, T.-A.; Park, S.; Kim, J. B.; Kim, T. K.; Seong, G. H.; Choo, J.; Kim, Y. S. (Sens. Actuators, B, 2011)

(untitled) - Yang, X.; Salles, V.; Kaneti, Y. V.; Liu, M.; Maillard, M.; Journet, C.; Jiang, X.; Brioude, A. (Sens. Actuators, B, 2015)

(untitled) - Wei, S.; Zhao, G.; Du, W.; Tian, Q. (Vacuum, 2016)

(untitled) - Choi, S.-W.; Park, J. Y.; Kim, S. S. (Chem. Eng. J., 2011)

(untitled) - Choi, J.-M.; Byun, J.-H.; Kim, S. S. (Sens. Actuators, B, 2016)

(untitled) - Yoon, J.-W.; Kim, H.-J.; Jeong, H.-M.; Lee, J.-H. (Sens. Actuators, B, 2014)

(untitled) - Yoon, J.-W.; Choi, J.-K.; Lee, J.-H. (Sens. Actuators, B, 2012)

(untitled) - Zheng, W.; Li, Z.; Zhang, H.; Wang, W.; Wang, Y.; Wang, C. (Mater. Res. Bull., 2009)

(untitled) - Fan, H.; Zhang, T.; Xu, X.; Lv, N. (Sens. Actuators, B, 2011)

(untitled) - Zhou, H.; Li, Z.; Niu, X.; Xia, X.; Wei, Q. (Ceram. Int., 2016)

(untitled) - Kim, I.-D.; Jeon, E.-K.; Choi, S.-H.; Choi, D.-K.; Tuller, H. L. (J. Electroceram., 2010)

(untitled) - Ab Kadir, R.; Li, Z.; Sadek, A. Z.; Abdul Rani, R.; Zoolfakar, A. S.; Field, M. R.; Ou, J. Z.; Chrimes, A. F.; Kalantar-zadeh, K. (J. Phys. Chem. C, 2014)

(untitled) - Cheng, L.; Ma, S. Y.; Wang, T. T.; Li, X. B.; Luo, J.; Li, W. Q.; Mao, Y. Z.; GZ, D. J. (Mater. Lett., 2014)

(untitled) - Li, T.; Zeng, W.; Zhao, W. (Mater. Lett., 2016)

(untitled) - Li, W. Q.; Ma, S. Y.; Luo, J.; Mao, Y. Z.; Cheng, L.; Gengzang, D. J.; Xu, X. L.; Yan, S. H. (Mater. Lett., 2014)

(untitled) - Cho, N. G.; Yang, D. J.; Jin, M.-J.; Kim, H.-G.; Tuller, H. L.; Kim, I.-D. (Sens. Actuators, B, 2011)

(untitled) - Wei, S.; Wang, S.; Zhang, Y.; Zhou, M. (Sens. Actuators, B, 2014)

(untitled) - Katoch, A.; Sun, G.-J.; Choi, S.-W.; Byun, J.-H.; Kim, S. S. (Sens. Actuators, B, 2013)

(untitled) - Katoch, A.; Abideen, Z. U.; Kim, J.-H.; Kim, S. S. (Sens. Actuators, B, 2016)

(untitled) - Cho, S.; Kim, D.-H.; Lee, B.-S.; Jung, J.; Yu, W.-R.; Hong, S.-H.; Lee, S. (Sens. Actuators, B, 2012)

(untitled) - Yu, X.; Song, F.; Zhai, B.; Zheng, C.; Wang, Y. (Phys. E (Amsterdam, Neth.), 2013)

(untitled) - Katoch, A.; Choi, S.-W.; Kim, H. W.; Kim, S. S. (J. Hazard. Mater., 2015)

(untitled) - Senthil, T.; Anandhan, S. (J. Colloid Interface Sci., 2014)

(untitled) - Trocino, S.; Frontera, P.; Donato, A.; Busacca, C.; Scarpino, L. A.; Antonucci, P.; Neri, G. (Mater. Chem. Phys., 2014)

(untitled) - Wang, L.; Cao, J.; Qian, X.; Zhang, H. (Mater. Lett., 2016)

(untitled) - Cao, J.; Dou, H.; Zhang, H.; Mei, H.; Liu, S.; Fei, T.; Wang, R.; Wang, L.; Zhang, T. (Sens. Actuators, B, 2014)

(untitled) - Lim, S. K.; Hwang, S.-H.; Chang, D.; Kim, S. (Sens. Actuators, B, 2010)

(untitled) - Xu, L.; Dong, B.; Wang, Y.; Bai, X.; Liu, Q.; Song, H. (Sens. Actuators, B, 2010)

(untitled) - Zheng, W.; Lu, X.; Wang, W.; Li, Z.; Zhang, H.; Wang, Y.; Wang, Z.; Wang, C. (Sens. Actuators, B, 2009)

(untitled) - Chi, X.; Liu, C.; Zhang, J.; Liu, L.; Li, H.; He, Y.; Bo, X.; Liu, L. (J. Semicond., 2014)

(untitled) - Lu, Q.; Wang, C.; Liu, S.; Ren, M. (Mater. Trans., 2011)

(untitled) - Park, J. Y.; Asokan, K.; Choi, S.-W.; Kim, S. S. (Sens. Actuators, B, 2011)

(untitled) - Kim, I.-D.; Rothschild, A. (Polym. Adv. Technol., 2011)

(untitled) - Jiang, C.; Zhang, G.; Wu, Y.; Li, L.; Shi, K. (CrystEngComm, 2012)

(untitled) - Landau, O.; Rothschild, A. (J. Electroceram., 2015)

(untitled) - Zhang, J.; Choi, S.-W.; Kim, S. S. (J. Solid State Chem., 2011)

(untitled) - Cui, J.; Shi, L.; Xie, T.; Wang, D.; Lin, Y. (Sens. Actuators, B, 2016)

(untitled) - Nikfarjam, A.; Salehifar, N. (Sens. Actuators, B, 2015)

(untitled) - Jiang, Z.; Yin, M.; Wang, C. (Mater. Lett., 2017)

(untitled) - Lee, D. Y.; Cho, J.-E.; Cho, N.-I.; Lee, M.-H.; Lee, S.-J.; Kim, B.-Y. (Thin Solid Films, 2008)

(untitled) - Liu, L.; Zhang, T.; Li, S.; Wang, L.; Tian, Y. (Mater. Lett., 2009)

(untitled) - Lotus, A. F.; Kang, Y. C.; Walker, J. I.; Ramsier, R. D.; Chase, G. G. (Mater. Sci. Eng., B, 2010)

(untitled) - Cacciotti, I.; Bianco, A.; Pezzotti, G.; Gusmano, G. (Chem. Eng. J., 2011)

(untitled) - Yamazoe, N.; Sakai, G.; Shimanoe, K. (Catal. Surv. Asia, 2003)

(untitled) - Yamazoe, N. (Sens. Actuators, B, 1991)

(untitled) - Kim, J.-H.; Zheng, Y.; Mirzaei, A.; Kim, S. S. (Korean J. Mater. Res., 2016)

(untitled) - Katoch, A.; Byun, J.-H.; Choi, S.-W.; Kim, S. S. (Sens. Actuators, B, 2014)

(untitled) - Xu, X.; Fan, H.; Liu, Y.; Wang, L.; Zhang, T. (Sens. Actuators, B, 2011)

(untitled) - Lee, J.-S.; Katoch, A.; Kim, J.-H.; Kim, S. S. (Sens. Actuators, B, 2016)

(untitled) - Xu, X.; Chen, Y.; Zhang, G.; Ma, S.; Lu, Y.; Bian, H.; Chen, Q. (J. Alloys Compd., 2017)

(untitled) - Xu, L.; Xing, R.; Song, J.; Xu, W.; Song, H. (J. Mater. Chem. C, 2013)

(untitled) - Miao, Y.-E.; He, S.; Zhong, Y.; Yang, Z.; Tjiu, W. W.; Liu, T. (Electrochim. Acta, 2013)

(untitled) - Ma, S.; Jia, J.; Tian, Y.; Cao, L.; Shi, S.; Li, X.; Wang, X. (Ceram. Int., 2016)

(untitled) - Wang, J.; Zou, B.; Ruan, S.; Zhao, J.; Chen, Q.; Wu, F. (Mater. Lett., 2009)

(untitled) - Kim, J. H.; Abideen, Z. U.; Zheng, Y.; Kim, S. S. (Sensors, 2016)

(untitled) - Shin, J.; Choi, S.-J.; Lee, I.; Youn, D.-Y.; Park, C. O.; Lee, J.-H.; Tuller, H. L.; Kim, I.-D. (Adv. Funct. Mater., 2013)

(untitled) - Jang, B.-H.; Landau, O.; Choi, S.-J.; Shin, J.; Rothschild, A.; Kim, I.-D. (Sens. Actuators, B, 2013)

(untitled) - Dong, K.-Y.; Choi, J.-K.; Hwang, I.-S.; Lee, J.-W.; Kang, B. H.; Ham, D.-J.; Lee, J.-H.; Ju, B.-K. (Sens. Actuators, B, 2011)

(untitled) - Zheng, W.; Lu, X.; Wang, W.; Li, Z.; Zhang, H.; Wang, Z.; Xu, X.; Li, S.; Wang, C. (J. Colloid Interface Sci., 2009)

(untitled) - Cho, N. G.; Woo, H.-S.; Lee, J.-H.; Kim, I.-D. (Chem. Commun., 2011)

(untitled) - Choi, S.-J.; Lee, I.; Jang, B.-H.; Youn, D.-Y.; Ryu, W.-H.; Park, C. O.; Kim, I.-D. (Anal. Chem., 2013)

(untitled) - Tang, W.; Wang, J.; Qiao, Q.; Liu, Z.; Li, X. (J. Mater. Sci., 2015)

(untitled) - Lin, Y.; Wei, W.; Li, Y.; Li, F.; Zhou, J.; Sun, D.; Chen, Y.; Ruan, S. (J. Alloys Compd., 2015)

(untitled) - Trung, D. D.; Hoa, N. D.; Tong, P. V.; Duy, N. V.; Dao, T. D.; Chung, H. V.; Nagao, T.; Hieu, N. V. (J. Hazard. Mater., 2014)

(untitled) - Choi, J.-K.; Hwang, I.-S.; Kim, S.-J.; Park, J.-S.; Park, S.-S.; Jeong, U.; Kang, Y. C.; Lee, J.-H. (Sens. Actuators, B, 2010)

(untitled) - Zhang, M.; Ning, T.; Zhang, S.; Li, Z.; Yuan, Z.; Cao, Q. (Mater. Sci. Semicond. Process., 2014)

(untitled) - Shahreen, L.; Chase, G. G.; Turinske, A. J.; Nelson, S. A.; Stojilovic, N. (Chem. Eng. J., 2013)

(untitled) - Moon, J.; Park, J.-A.; Lee, S.-J.; Zyung, T.; Kim, I.-D. (Sens. Actuators, B, 2010)

(untitled) - Wei, S.; Yu, Y.; Zhou, M. (Mater. Lett., 2010)

(untitled) - Jiang, Z.; Jiang, T.; Wang, J.; Wang, Z.; Xu, X.; Wang, Z.; Zhao, R.; Li, Z.; Wang, C. (J. Colloid Interface Sci., 2015)

(untitled) - Wang, Z.; Liu, L. (Mater. Lett., 2009)

(untitled) - Cheng, J. P.; Wang, B. B.; Zhao, M. G.; Liu, F.; Zhang, X. B. (Sens. Actuators, B, 2014)

(untitled) - Liu, L.; Zhang, T.; Wang, L.; Li, S. (Mater. Lett., 2009)

(untitled) - Xu, X.; Sun, J.; Zhang, H.; Wang, Z.; Dong, B.; Jiang, T.; Wang, W.; Li, Z.; Wang, C. (Sens. Actuators, B, 2011)

(untitled) - Xiong, Y.; Xue, Q.; Ling, C.; Lu, W.; Ding, D.; Zhu, L.; Li, X. (Sens. Actuators, B, 2017)

(untitled) - Jang, J.-S.; Kim, S.-J.; Choi, S.-J.; Kim, N.-H.; Hakim, M.; Rothschild, A.; Kim, I.-D. (Nanoscale, 2015)

(untitled) - Wu, J.; Huang, Q.; Zeng, D.; Zhang, S.; Yang, L.; Xia, D.; Xiong, Z.; Xie, C. (Sens. Actuators, B, 2014)

(untitled) - Kou, X.; Wang, C.; Ding, M.; Feng, C.; Li, X.; Ma, J.; Zhang, H.; Sun, Y.; Lu, G. (Sens. Actuators, B, 2016)

(untitled) - Liu, L.; Guo, C.; Li, S.; Wang, L.; Dong, Q.; Li, W. (Sens. Actuators, B, 2010)

(untitled) - Kukkola, J.; Mohl, M.; Leino, A.-R.; Mäklin, J.; Halonen, N.; Shchukarev, A.; Konya, Z.; Jantunen, H.; Kordas, K. (Sens. Actuators, B, 2013)

(untitled) - Koo, W.-T.; Choi, S.-J.; Kim, N.-H.; Jang, J.-S.; Kim, I.-D. (Sens. Actuators, B, 2016)

(untitled) - Kim, K.-H.; Kim, S.-J.; Cho, H.-J.; Kim, N.-H.; Jang, J.-S.; Choi, S.-J.; Kim, I.-D. (Sens. Actuators, B, 2017)

(untitled) - Cho, H.-J.; Kim, S.-J.; Choi, S.-J.; Jang, J.-S.; Kim, I.-D. (Sens. Actuators, B, 2017)

(untitled) - Kim, S.-J.; Choi, S.-J.; Jang, J.-S.; Cho, H.-J.; Koo, W.-T.; Tuller, H. L.; Kim, I.-D. (Adv. Mater., 2017)

(untitled) - Koo, W.-T.; Jang, J.-S.; Choi, S.-J.; Cho, H.-J.; Kim, I.-D. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Li, W.; Ma, S.; Yang, G.; Mao, Y.; Luo, J.; Cheng, L.; Gengzang, D.; Xu, X.; Yan, S. (Mater. Lett., 2015)

(untitled) - Sun, Y.; Zhao, Z.; Li, P.; Li, G.; Chen, Y.; Zhang, W.; Hu, J. (Appl. Surf. Sci., 2015)

(untitled) - Xu, X. L.; Chen, Y.; Ma, S. Y.; Li, W. Q.; Mao, Y. Z. (Sens. Actuators, B, 2015)

(untitled) - Zhao, M.; Wang, X.; Ning, L.; Jia, J.; Li, X.; Cao, L. (Sens. Actuators, B, 2011)

(untitled) - Mao, Y.; Ma, S.; Li, X.; Wang, C.; Li, F.; Yang, X.; Zhu, J.; Ma, L. (Appl. Surf. Sci., 2014)

(untitled) - Liu, L.; Li, S.; Zhuang, J.; Wang, L.; Zhang, J.; Li, H.; Liu, Z.; Han, Y.; Jiang, X.; Zhang, P. (Sens. Actuators, B, 2011)

(untitled) - Zhao, M.; Wang, X.; Cheng, J.; Zhang, L.; Jia, J.; Li, X. (Curr. Appl. Phys., 2013)

(untitled) - Huang, B.; Zhao, C.; Zhang, M.; Zhang, Z.; Xie, E.; Zhou, J.; Han, W. (Appl. Surf. Sci., 2015)

(untitled) - Park, D.-H.; Son, K.-Y.; Lee, J.-H.; Kim, J.-J.; Lee, J.-S. (Solid State Ionics, 2004)

(untitled) - Lotus, A. F.; Kang, Y. C.; Ramsier, R. D.; Chase, G. G. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2009)

(untitled) - Feng, Y.; Hou, W.; Zhang, X.; Lv, P.; Li, Y.; Feng, W. (J. Phys. Chem. C, 2011)

(untitled) - Han, N.; Chai, L.; Wang, Q.; Tian, Y.; Deng, P.; Chen, Y. (Sens. Actuators, B, 2010)

(untitled) - Zhao, C.; Bai, J.; Huang, B.; Wang, Y.; Zhou, J.; Xie, E. (Sens. Actuators, B, 2016)

(untitled) - Shan, H.; Liu, C.; Liu, L.; Li, S.; Wang, L.; Zhang, X.; Bo, X.; Chi, X. (Sens. Actuators, B, 2013)

(untitled) - Su, C.; Zou, Y.; Xu, X.; Liu, L.; Liu, Z.; Liu, L. (Colloids Surf., A, 2015)

(untitled) - Su, C.; Liu, C.; Liu, L.; Ni, M.; Li, H.; Bo, X.; Liu, L.; Chi, X. (Appl. Surf. Sci., 2014)

(untitled) - Su, C.; Li, Y.; He, Y.; Liu, L.; Wang, X.; Liu, L. (Mater. Sci. Semicond. Process., 2015)

(untitled) - Li, Z.; Dzenis, Y. (Talanta, 2011)

(untitled) - Wang, X.; Li, H.; Ni, M.; Wang, L.; Liu, L.; Wang, H.; Guo, X. (J. Electron. Mater., 2017)

(untitled) - Lian, H.; Wang, G.; Yue, H.; Liu, L.; Guo, X.; Wang, X. (Micro Nano Lett., 2016)

(untitled) - Wang, X. S.; Wang, G. G.; Li, H. Y.; Wang, L. Y.; Liu, L.; Guo, X. X.; Wang, H.; Lian, H. W. (Wuli Xuebao, 2016)

(untitled) - Xu, L.; Dong, B.; Wang, Y.; Bai, X.; Chen, J.; Liu, Q.; Song, H. (J. Phys. Chem. C, 2010)

(untitled) - Zhao, C.; Huang, B.; Xie, E.; Zhou, J.; Zhang, Z. (Sens. Actuators, B, 2015)

(untitled) - Wang, X.; Zhang, J.; Wang, L.; Li, S.; Liu, L.; Su, C.; Liu, L. (J. Mater. Sci. Technol., 2015)

(untitled) - Liu, J.; Guo, W.; Qu, F.; Feng, C.; Li, C.; Zhu, L.; Zhou, J.; Ruan, S.; Chen, W. (Ceram. Int., 2014)

(untitled) - Liu, C.; Wang, X.; Xie, F.; Liu, L.; Ruan, S. (J. Mater. Sci.: Mater. Electron., 2016)

(untitled) - Lian, H.; Feng, Y.; Wang, Z.; Liu, L.; Guo, X.; Wang, X. (Appl. Phys. A: Mater. Sci. Process., 2017)

(untitled) - Feng, C.; Wang, C.; Zhang, H.; Li, X.; Wang, C.; Cheng, P.; Ma, J.; Sun, P.; Gao, Y.; Zhang, H.; Sun, Y.; Zheng, J.; et al. (Sens. Actuators, B, 2015)

(untitled) - Wang, Y.; Zhang, H.; Sun, X. (Appl. Surf. Sci., 2016)

(untitled) - Wan, G. X.; Ma, S. Y.; Sun, X. W.; Sun, A. M.; Li, X. B.; Luo, J.; Li, W. Q.; Wang, C. Y. (Mater. Lett., 2015)

(untitled) - Li, W.; Ma, S.; Li, Y.; Yang, G.; Mao, Y.; Luo, J.; Gengzang, D.; Xu, X.; Yan, S. (Sens. Actuators, B, 2015)

(untitled) - Katoch, A.; Kim, J.-H.; Kim, S. S. (J. Nanosci. Nanotechnol., 2015)

(untitled) - Xu, L.; Song, H.; Dong, B.; Wang, Y.; Chen, J.; Bai, X. (Inorg. Chem., 2010)

(untitled) - Gao, J.; Wang, L.; Kan, K.; Xu, S.; Jing, L.; Liu, S.; Shen, P.; Li, L.; Shi, K. (J. Mater. Chem. A, 2014)

(untitled) - Xu, S.; Gao, J.; Wang, L.; Kan, K.; Xie, Y.; Shen, P.; Li, L.; Shi, K. (Nanoscale, 2015)

(untitled) - Wu, H.; Kan, K.; Wang, L.; Zhang, G.; Yang, Y.; Li, H.; Jing, L.; Shen, P.; Li, L.; Shi, K. (CrystEngComm, 2014)

(untitled) - Chi, X.; Liu, C.; Liu, L.; Li, S.; Li, H.; Zhang, X.; Bo, X.; Shan, H. (Mater. Sci. Semicond. Process., 2014)

(untitled) - Lee, C.-S.; Kim, I.-D.; Lee, J.-H. (Sens. Actuators, B, 2013)

(untitled) - Liu, J.; Li, X.; Chen, X.; Niu, H.; Han, X.; Zhang, T.; Lin, H.; Qu, F. (New J. Chem., 2016)

(untitled) - Du, H.; Wang, J.; Sun, Y.; Yao, P.; Li, X.; Yu, N. (Sens. Actuators, B, 2015)

(untitled) - Deng, J.; Yu, B.; Lou, Z.; Wang, L.; Wang, R.; Zhang, T. (Sens. Actuators, B, 2013)

(untitled) - Lou, Z.; Li, F.; Deng, J.; Wang, L.; Zhang, T. (ACS Appl. Mater. Interfaces, 2013)

(untitled) - Lou, Z.; Deng, J.; Wang, L.; Wang, R.; Fei, T.; Zhang, T. (RSC Adv., 2013)

(untitled) - Qi, Q.; Wang, P.-P.; Zhao, J.; Feng, L.-L.; Zhou, L.-J.; Xuan, R.-F.; Liu, Y.-P.; Li, G.-D. (Sens. Actuators, B, 2014)

(untitled) - Nikfarjam, A.; Salehifar, N. (IEEE Sens. J., 2015)

(untitled) - Wang, Q.; Dong, X.; Pang, Z.; Du, Y.; Xia, X.; Wei, Q.; Huang, F. (Sensors, 2012)

(untitled) - Li, Y.; Gong, J.; He, G.; Deng, Y. (Mater. Chem. Phys., 2011)

(untitled) - Wang, Y.; Jia, W.; Strout, T.; Ding, Y.; Lei, Y. (Sensors, 2009)

(untitled) - Li, Y.; Ban, H.; Yang, M. (Sens. Actuators, B, 2016)

(untitled) - Li, Y.; Ban, H.; Jiao, M.; Yang, M. (RSC Adv., 2016)

(untitled) - Wang, Z.; Liu, S.; Jiang, T.; Xu, X.; Zhang, J.; An, C.; Wang, C. (RSC Adv., 2015)

(untitled) - Yan, S.; Wu, Q. (Sens. Actuators, B, 2014)

(untitled) - Abideen, Z. U.; Park, J. Y.; Kim, H. W.; Kim, S. S. (Nanotechnology, 2017)

(untitled) - Kim, J.-H.; Zheng, Y.; Mirzaei, A.; Kim, H. W.; Kim, S. S. (J. Electron. Mater., 2017)

(untitled) - Liu, S.; Sun, H.; Nagarajan, R.; Kumar, J.; Gu, Z.; Cho, J.; Kurup, P. (Sens. Actuators, A, 2011)

(untitled) - Lin, Q.; Li, Y.; Yang, M. (Anal. Chim. Acta, 2012)

(untitled) - He, X.; Arsat, R.; Sadek, A. Z.; Wlodarski, W.; Kalantar-zadeh, K.; Li, J. (Sens. Actuators, B, 2010)

(untitled) - Matatagui, D.; Fernández, M. J.; Santos, J. P.; Fontecha, J.; Sayago, I.; Horrillo, M. C.; Grácia, I.; Cané, C. (J. Nanomater., 2014)

(untitled) - Liu, Y.; Huang, H.; Wang, L.; Cai, D.; Liu, B.; Wang, D.; Li, Q.; Wang, T. (Sens. Actuators, B, 2016)

(untitled) - Sheng, L.; Dajing, C.; Yuquan, C. (Nanotechnology, 2011)

Applications of piezoelectric quartz crystal microbalances - Lu, C.; Czanderna, A. W. (Elsevier, 2012)

(untitled) - Sauerbrey, G. (Z. Phys., 1959)

(untitled) - Wang, Z. L.; Wu, W. (Angew. Chem., Int. Ed., 2012)

(untitled) - Aria, M. M.; Irajizad, A.; Astaraei, F. R.; Shariatpanahi, S. P.; Sarvari, R. (Measurement, 2016)

(untitled) - Zhang, C.; Wang, X.; Lin, J.; Ding, B.; Yu, J.; Pan, N. (Sens. Actuators, B, 2011)

(untitled) - Ding, B.; Wang, X.; Yu, J.; Wang, M. (J. Mater. Chem., 2011)

(untitled) - Wang, X.; Wang, J.; Si, Y.; Ding, B.; Yu, J.; Sun, G.; Luo, W.; Zheng, G. (Nanoscale, 2012)

(untitled) - Ding, B.; Yamazaki, M.; Shiratori, S. (Sens. Actuators, B, 2005)

(untitled) - Wang, X.; Ding, B.; Yu, J.; Si, Y.; Yang, S.; Sun, G. (Nanoscale, 2011)

(untitled) - Jia, Y.; Yan, C.; Yu, H.; Chen, L.; Dong, F. (Sens. Actuators, B, 2014)

(untitled) - Jia, Y.; Yu, H.; Zhang, Y.; Chen, L.; Dong, F. (Sens. Actuators, B, 2015)

(untitled) - Ding, B.; Kim, J.; Miyazaki, Y.; Shiratori, S. (Sens. Actuators, B, 2004)

(untitled) - Hu, Y.; Yu, H.; Yan, Z.; Ke, Q. (RSC Adv., 2018)

(untitled) - Huang, W.; Wang, X.; Jia, Y.; Li, X.; Zhu, Z.; Li, Y.; Si, Y.; Ding, B.; Wang, X.; Yu, J. (RSC Adv., 2013)

(untitled) - Horzum, N.; Tascioglu, D.; Özbek, C.; Okur, S.; Demir, M. M. (New J. Chem., 2014)

(untitled) - Jia, Y.; Chen, L.; Yu, H.; Zhang, Y.; Dong, F. (RSC Adv., 2015)

(untitled) - Korotcenkov, G. (Mater. Sci. Eng., B, 2007)

(untitled) - Sekimoto, S.; Nakagawa, H.; Okazaki, S.; Fukuda, K.; Asakura, S.; Shigemori, T.; Takahashi, S. (Sens. Actuators, B, 2000)

(untitled) - Viter, R.; Chaaya, A. A.; Iatsunskyi, I.; Nowaczyk, G.; Kovalevskis, K.; Erts, D.; Miele, P.; Smyntyna, V.; Bechelany, M. (Nanotechnology, 2015)

(untitled) - Luoh, R.; Hahn, H. T. (Compos. Sci. Technol., 2006)

(untitled) - Aydogdu, S.; Ertekin, K.; Suslu, A.; Ozdemir, M.; Celik, E.; Cocen, U. (J. Fluoresc., 2011)

(untitled) - Xue, W.; Zhang, Y.; Duan, J.; Liu, D.; Ma, Y.; Shi, N.; Chen, S.; Xie, L.; Qian, Y.; Huang, W. (J. Mater. Chem. C, 2015)

(untitled) - Urrutia, A.; Goicoechea, J.; Rivero, P. J.; Matías, I. R.; Arregui, F. J. (Sens. Actuators, B, 2013)

(untitled) - Davis, B. W.; Burris, A. J.; Niamnont, N.; Hare, C. D.; Chen, C.-Y.; Sukwattanasinitt, M.; Cheng, Q. (Langmuir, 2014)

(untitled) - Xue, R.; Behera, P.; Xu, J.; Viapiano, M. S.; Lannutti, J. J. (Sens. Actuators, B, 2014)

(untitled) - Wolf, C.; Tscherner, M.; Köstler, S. (Sens. Actuators, B, 2015)

2014 IEEE Proceedings of Sensors - Wolf, C.; Tscherner, M.; Köstler, S.; Ribitsch, V. (Optochemical sensors based on polymer nanofibers with ultra-fast response characteristics, 2014)

(untitled) - Zhang, Y.; He, X.; Li, J.; Miao, Z.; Huang, F. (Sens. Actuators, B, 2008)

(untitled) - Park, J.-A.; Moon, J.; Lee, S.-J.; Lim, S.-C.; Zyung, T. (Curr. Appl. Phys., 2009)

(untitled) - Liu, Y.; Gao, C.; Pan, X.; An, X.; Xie, Y.; Zhou, M.; Song, J.; Zhang, H.; Liu, Z.; Zhao, Q.; Zhang, Y.; Xie, E. (Appl. Surf. Sci., 2011)

(untitled) - Sowti Khiabani, P.; Hosseinmardi, A.; Marzbanrad, E.; Ghashghaie, S.; Zamani, C.; Keyanpour-Rad, M.; Raissi, B. (Sens. Actuators, B, 2012)

(untitled) - Karimi, E. Z.; Esmaeilzadeh, J.; Marzbanrad, E. (Bull. Mater. Sci., 2015)

(untitled) - Liang, X.; Kim, T.-H.; Yoon, J.-W.; Kwak, C.-H.; Lee, J.-H. (Sens. Actuators, B, 2015)

(untitled) - Qi, Q.; Zou, Y.-C.; Fan, M.-H.; Liu, Y.-P.; Gao, S.; Wang, P.-P.; He, Y.; Wang, D.-J.; Li, G.-D. (Sens. Actuators, B, 2014)

(untitled) - Song, X.; Liu, L. (Sens. Actuators, A, 2009)

(untitled) - Zhang, H.-D.; Tang, C.-C.; Long, Y.-Z.; Zhang, J.-C.; Huang, R.; Li, J.-J.; Gu, C.-Z. (Sens. Actuators, A, 2014)

(untitled) - Bai, H.; Zhao, L.; Lu, C.; Li, C.; Shi, G. (Polymer, 2009)

(untitled) - Low, K.; Horner, C. B.; Li, C.; Ico, G.; Bosze, W.; Myung, N. V.; Nam, J. (Sens. Actuators, B, 2015)

(untitled) - Patil, P. T.; Anwane, R. S.; Kondawar, S. B. (Procedia Mater. Sci., 2015)

(untitled) - Pang, Z.; Nie, Q.; Wei, A.; Yang, J.; Huang, F.; Wei, Q. (J. Mater. Sci., 2017)

(untitled) - Pinto, N. J.; Ramos, I.; Rojas, R.; Wang, P.-C.; Johnson, A. T., Jr (Sens. Actuators, B, 2008)

(untitled) - Pinto, N. J.; Rivera, D.; Melendez, A.; Ramos, I.; Lim, J. H.; Johnson, A. T. C. (Sens. Actuators, B, 2011)

(untitled) - Feng, Q.; Li, X.; Wang, J.; Gaskov, A. M. (Sens. Actuators, B, 2016)

(untitled) - Han, L.; Andrady, A. L.; Ensor, D. S. (Sens. Actuators, B, 2013)

(untitled) - Lv, Y.-Y.; Wu, J.; Xu, Z.-K. (Sens. Actuators, B, 2010)

(untitled) - Zhou, Q.; Sussman, A.; Chang, J.; Dong, J.; Zettl, A.; Mickelson, W. (Sens. Actuators, A, 2015)